Influence of hepatitis c in the development of histological and morfological changes in the placenta - O. M. Filipovich; N. I. Kuznetsov; V. E. Karev; E. A. Malahovskaya (Журнал инфектологии, 2016)
The purpose: detection of morphological changes of fetoplacental complex in pregnant women with chronic hepatitis C.Methods: The study involved 48 pregnant women , 38 of them with chronic hepatitis C and 10 – healthy pregnant women without complicated obstetric – gynecological history. Do all women was conducted morphological and histological study of their placentas. Placental tissue samples were fixed in 10% formalin solution. After fixation in 10% neutral formalin, the samples were subjected to histological wiring placentas by incubation in isopropyl alcohol and paraffin imbibition using the apparatus for automatic wiring histological samples gated Exelsior (Thermo, Germany) .Immunogistohimicheskie (IHC) studies were performed using a mouse monoclonal antibody NS3-antigen to hepatitis C virus (at a dilution of 1/80, Novocastra Lab., UK).Results: chronic ( sub) compensated placental insufficiency often revealed by the presence of NS3-HCV in the placenta. In the presence of placental infection with hepatitis C virus ( HCV NS3 ) , the presence of more common detsiduita placenta.Conclusions: Hepatitis C virus is one of the most important factors in the development of chronic placental insufficiency.